The Venture Bros. 3rd season [videorecording (DVD)] - Urbaniak, James, 1963-; Warburton, Patrick; Sinterniklaas, Michael; McCulloch, Chris (Warner Home Video, 2009)
"Witness the genesis of villainous personae, the clash of sporadically opposing forces, and the birth of debilitating neuroses in this, the sturmiest, most drangful season yet."--Container. Includes 13 uncensored episodes